Aramaic graffiti from Hatra : a study based on the archive of the Missione Archeologica Italiana - Moriggi, Marco, (Culture and History of the Ancient Near East, 2019)
Graffiti are an often neglected but crucial witness to everyday life of ancient civilizations. The Aramaic graffiti from Hatra (North Iraq) can make an invaluable contribution in this sense, distributed as they were in various buildings throughout this city which flourished between the 1st and the Third century AD. Thanks to an effective interaction between epigraphy and archaeology, Marco Moriggi and Ilaria Bucci offer a thorough analysis of the Aramaic graffiti from Hatra as documented by the Archive of the Missione Archeologica Italiana (Turin). In addition to the edition of 48 published and 37 unpublished graffiti, this study further includes the concordances of numbers of all Hatran texts published so far and full archaeological information about the graffiti.